2012
DOI: 10.1371/journal.pone.0038611
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Populations Evolve to Greater Race Complexity in Agricultural Systems – Evidence from Analysis of Rhynchosporium secalis Virulence Data

Abstract: Fitness cost associated with pathogens carrying unnecessary virulence alleles is the fundamental assumption for preventing the emergence of complex races in plant pathogen populations but this hypothesis has rarely been tested empirically on a temporal and spatial scale which is sufficient to distinguish evolutionary signals from experimental error. We analyzed virulence characteristics of ∼1000 isolates of the barley pathogen Rhynchosporium secalis collected from different parts of the United Kingdom between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
1
18
0
1
Order By: Relevance
“…As observed in other agricultural pathogens (Zhan et al. ; Zhan and McDonald ), results for P. coronata demonstrate considerable variation in virulence level among individuals, and in the frequencies of specific virulence alleles over the geographic range (this report; Carson , ). We posit that historical breeding practices and landscape level demographic processes generate selection for increased host genotype range that outweigh the constraints imposed by costs at smaller spatial or temporal scales.…”
Section: Discussionsupporting
confidence: 78%
“…As observed in other agricultural pathogens (Zhan et al. ; Zhan and McDonald ), results for P. coronata demonstrate considerable variation in virulence level among individuals, and in the frequencies of specific virulence alleles over the geographic range (this report; Carson , ). We posit that historical breeding practices and landscape level demographic processes generate selection for increased host genotype range that outweigh the constraints imposed by costs at smaller spatial or temporal scales.…”
Section: Discussionsupporting
confidence: 78%
“…It suggests that one unforeseen consequence of widespread deployment of quantitatively resistant cultivars or intensive application of synthetic antimicrobials might be selection for a higher basal level of antimicrobial resistance and enhanced virulence in pathogen populations, which would pose a greater threat to agricultural production. In this case, more dynamic disease management programs that incorporate more rapid spatial and temporal turnover of host resistance or synthetic antimicrobials may be important for sustainable disease control [74]. More rapid spatial and temporal turnover of host resistance or antimicrobials is expected to generate fluctuating selection against pathogens that could prevent the emergence of pathogen individuals and populations with higher virulence and antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Results from other studies suggested that the ability of R. commune to adapt in response to changes in host resistance or host diversity is high. The pathogen was shown to evolve simpler races when host diversity is low (Jackson & Webster, 1976b) or more complex races when host diversity is high (Zhang et al, 1992;Zhan et al, 2012). Furthermore, it was shown to quickly overcome major resistance genes deployed in host cultivars (Xi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%